ASR, Volume 21, n° 2, 2017 - Full Issue - journal system, (African Sociological Review, 2017)
Contents Editorial ..............................................................1 General Issues Postcolonial debates in Germany Elise Pape ...................................................2 Women in postcolonial societies: Reflection on women and peacebuilding in Northern Uganda Erich Awich Ochen .................................................15 Research Papers Rural-Urban Disparities in Health and Health Care: Cultural competence and Lay beliefs in the Narratives of Diabetes among the rural poor in the Eastern Cape Province of South Africa Olajide Oloyede .......................................................36 Gender Revolution Prospects in Nigeria: Implications for Marriage Timing and Fertility Onipede Wusu & A. Adedokun ..........................................58 Party Identification and Service Delivery Protests in the Eastern Cape and Northern Cape, South Africa Suthulego Matebesi & Lucius Botes ..............................................81 The Social Act of Exchange in Power Relations: The study of the Phenomenon of Nichekeleko at the Weighbridges in Zambia. Chidongo Phiri ...............................................100 Non-meritocratic Factors and Recruitment Process in Oyo State Civil Service, Nigeria Adebimpe A. Adenugba, Omolayo Fadoju & Ruth E. Akhuetie ...........................115